IMPLEMENTATION OF GOVERNMENT REGULATION NUMBER 23 OF 2018 IN DIRECTORATE GENERAL OF TAXES (DGT) II CENTRAL JAVA - desy nur pratiwi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2020)
The government reduced the tax rates of UMKM that were originally 1% to 0.5% to increase taxpayer compliance. The purpose of this study is to find out the number of taxpayers and the level of tax revenue of UMKM after government regulation (PP) number 23 of 2018. The population in this study is the UMKM taxpayer at the Directorate General of Tax (DJP) of Central Java Region II. This type of research is in the form of descriptive research that is by describing data from the Central Java Region II DGT. The results of this study are the number of taxpayers before PP 23 of 2018 was 232,327 UMKM and the amount of tax revenue was Rp. 124,123,577,989.00 after the PP 23 of 2018 the number of mandatory increased by 48,474 UMKM but the amount of tax revenue has decreased by Rp. 18,344,874,319.00.